Controllable Growth of the ZnO Nanorod Arrays on the Al Substrate and Their Reversible Wettability Transition. (23rd February 2017) - Li, Hong; Liu, Hongyan; Li, Yushan; Liu, Qinzhuang
Abstract : High-quality ZnO nanorod arrays are formed using the ZnO nanoflakes on the Al substrate as seed layer. A reversible wettability transition can be easily achieved via alternation of UV irradiation and dark storage. The physical adsorption of the water molecules on the surface of ZnO nanorod arrays is considered to be responsible for this transition, which is confirmed by X-ray photoelectron spectroscopy.